القيم الأخلاقية عند المراهقين مقوماتها وتحدياتها في ضوء القرآن والسنة مدارس العاصمة داكا أنموذجًا \ - حسن، محمد نجم (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
This study aimed to highlight the topic of adolescent moral values and their challenges and detractions in the light of the Qur'an and Sunnah. The challenges and detractions come in many forms; mostly from and through digital technology and their contents. This research utilized the inductive method to find verses and Hadith which are associated with moral development and analytical method to analyze vital reasons for moral deviation. The researcher also used the critical method to evaluate the adolescent condition in society, politics, family, and the impact of contents found on many digital platorms. A questionnaire was distributed among students in four schools in the capital of Bangladesh. The research reached some importatn conclusions such as: the general education system in Bangladesh is inspired by a western secular education system. Parents should monitor their children constantly so that they do not get the opportunity to enter and browse immoral websites through internet. They should not allow the children to browse the internet in a locked room and should fix time for it. All these efforts should be with kindness, advices, and loving approach.